Analisis Penerapan Strategi Internasional oleh PT Indofood CBP Sukses Makmur Tbk. - June Alvina; Adi Neka Fatyandri; Khesi; William; Maryati; Selina. Ng (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
International strategy is an approach used by companies to expand and sell products/services outside of their domestic market. In implementing an international strategy, companies need to consider the culture and regulations of the destination country, as well as the company's conditions to determine the right mode of entry. This study aims to analyze the application of ICBP's international strategy and mode of entry in entering the global market. This type of research is in the form of qualitative research with qualitative descriptive analysis methods. Through this research, the authors managed to find that the international strategy implemented by ICBP is a multidomestic strategy with modes of entry in the form of exports, strategic alliances, acquisitions, and the establishment of factories abroad. It is hoped that through this research, ICBP can continue to expand its presence in the international market by utilizing the company's SWOT